High-speed signal propagation : advanced black magic. - Johnson, Howard W., ....-; Graham, Martin, ....- (Upper Saddle River : Prentice Hall, 2003)
This book is a companion to the original book by Johnson and Graham, High-Speed Digital Design- A Handbook of Black Magic, Prentice-Hall, 1993. The two books may be used separately, or together. They cover different material. KEY TOPICS- High-Speed Signal Propagation delves into the issues relevant to signal transmission at the upper limits of speed and distance. This book shows you how to transmit faster and further than ever before, considering today's digital networks and wireless devices. You'll find it packed with practical advice, including material never before published on the subject of high-speed design. Johnson also presents a complete and unified theory of signal propagation for all metallic media from cables to pcb traces to chips. It includes numerous examples, pictures, tables, and wide-ranging discussion of the high-speed properties of transmission lines. This is not yet another book on the subject of ringing and crosstalk. It's about long, high-speed channels operating at the upper limits of speed and distance. EDN Magazine will feature and 1- 1/2 page excerpt from Johnson's book each month, for seven months leading up to the book's publication. MARKET- The reader should know what a transmission line is, and have some general understanding of the relationship between the time domain and the frequency domain. Digital logic designers, system architects, EMC specialists, technicians, and printed wiring layout professionals. Anyone who works with long, high-speed signal channels fighting tradeoffs between speed and distance.
Keywords: Digitale technieken